Benzodiazepines for psychosis-induced aggression or agitation - Zaman, Hadar; Sampson, Stephanie J; Beck, Alison Ls; Sharma, Tarang; Clay, Fiona J; Spyridi, Styliani; Zhao, Sai; Gillies, Donna (My University, 2018)
Acute psychotic illness, especially when associated with agitated or violent behavior, can require urgent pharmacological tranquillization or sedation. In many countries, benzodiazepines (either alone or in combination with antipsychotics) are often used in this situation (1).
Keywords: Tranquilisation; Adverse; Effects; Benzodiazepine